Extremely low‐frequency electromagnetic fields accelerates wound healing modulating MMP‐9 and inflammatory cytokines. (22nd January 2018) - Patruno, A.; Ferrone, A.; Costantini, E.; Franceschelli, S.; Pesce, M.; Speranza, L.; Amerio, P.; D'Angelo, C.; Felaco, M.; Grilli, A.; Reale, M.
Abstract: Objectives: In our previous reports, we have demonstrated that extremely low‐frequency electromagnetic fields (ELF‐EMF) exposure enhances the proliferation of keratinocyte. The present study aimed to clarify effects of ELF‐EMF on wound healing and molecular mechanisms involved, using a scratch in vitro model. Materials and methods: The wounded monolayer cultures of human immortalized keratinocytes (HaCaT), at different ELF‐EMF and Sham exposure times were monitored under an inverted microscope. The production and expression of IL‐1β, TNF‐α, IL‐18 and IL‐18BP were measured by enzyme‐linked immunosorbent assay and quantitative real‐time PCR. The activity and the expression of matrix metalloproteinases (MMP)‐2/9 was evaluated by zymography and Western blot analysis, respectively. Signal transduction proteins expression (Akt and ERK) was measured by Western blot. Results: The results of wound healing in vitro assay revealed a significant reduction of cell‐free area time‐dependent in ELF‐EMF‐exposed cells compared to Sham condition. Gene expression and release of cytokines analysed were significantly increased in ELF‐EMF‐exposed cells. Our results further showed that ELF‐EMF exposure induced the activity and expressions of MMP‐9. Molecular data showed that effects of ELF‐EMF might be mediated via Akt and ERK signal pathway, as demonstrated using their specific inhibitors. Conclusions: Our results highlight ability of ELF‐EMF to modulate inflammation mediators and keratinocyte proliferation/migration, playing an important role in wound repair. The ELF‐EMF accelerates wound healing modulating expression of the MMP‐9 via Akt/ERK pathway.